Silent Suffering: Recognizing and Addressing the Emotional Impact of Patient Loss on Medical Students - Grace Kim (University Library System, University of Pittsburgh, 2024)
Experiencing patient loss is emotionally challenging for many medical students. This narrative reflects on the author's encounter with sudden patient loss and the complex emotions it evoked. The commentary underscores the need to prioritize emotional support for medical students dealing with patient loss. The author proposes ways to accomplish this, including equipping students with effective coping mechanisms, creating a supportive environment that encourages students to seek debriefing sessions, and incorporating debriefing sessions into clerkship curricula. By normalizing the emotional complexities of patient loss and fostering a culture of support, medical education can better prepare students to navigate the challenges of patient care with compassion and resilience.